Altitudinal zonation of tropical rain forest at the Danum Valley - H. Adam, Jumaat; L. Enning, Ferdinand (Malaysian Journal of Science (MJS), 1996)
Clustering analysis of forest community types at the Danum Valley Tropical Rain Forest Research Centre, Sabah, Ma-laysia using complete linkage method and average linkage method has been carried out. The analysis resulted in the identification of four forest types/zones. To determine the dominant and codominant species within each forest zone, the highest and second highest im-portance values (I„) of all tree species were calculated. In forest zone 1 (FZ1), at 150-250 m a.s.1., the dominant and codominant species are respectively, Shorea pauciflora and Shorea fallax; in forest zone 2 (FZ2), at 350-500 m altitude, Shorea leprosula and Vatica dulitensis; in forest zone 3 (FZ3), at 600-700 m, Shorea pauciflora and Vatica dulitensis; and in forest zone 4 (FZ4) or sum-mit zone, at 820 m, are Schima wallichii and Ternstroemia aneura. Forest zones 1 and 2 share many common attributes: both zones comprise three tree-canopy layers, i.e. emergent, main canopy and lower storey; both the dominant and codominant species belong to the family Dipterocarpaceae; both containing a high number of fami-lies and species; in terms of species richness, the two dominant fami-lies are the Euphorbiaceae and the Dipterocarpaceae; more than 70% of the families with a dbh of >3 cm contributed less than 10 stems each. Forest zone 3 (FZ3), occurring at higher altitude, differs from FZ1 and FZ2 in its two tree-storeys (main canopy and lower storey) and the Myrtaceae being the second dominant family in terms of species richness and density. The summit zone (FZ4) differs mark-edly from FZ1, FZ2 and FZ3 in having one tree-layer, comprising of trees of lower height and small diameter; the dominant and codominant species being Schima wallichii and Ternstroemia aneura of the Theaceae instead of Dipterocarpaceae; and the number of species and families and species diversity value are lower. In physi-ognomy, forest zone 4 is similar to that of the typical high altitude montane mossy forest in Sabah, thus demonstrating the Massenerhebung effect. There is a decrease in species and family richness, species diversity, tree height and diameter, above ground biomass, basal area, and stratification with increasing altitude. Conversely, tree density and frequency of small sized trees increase with increasing altitude.